2020
DOI: 10.1016/j.redox.2020.101648
|View full text |Cite
|
Sign up to set email alerts
|

CMS121, a fatty acid synthase inhibitor, protects against excess lipid peroxidation and inflammation and alleviates cognitive loss in a transgenic mouse model of Alzheimer's disease

Abstract: The oxidative degradation of lipids has been shown to be implicated in the progression of several neurodegenerative diseases and modulating lipid peroxidation may be efficacious for treating Alzheimer’s disease (AD). This hypothesis is strengthened by recent findings suggesting that oxytosis/ferroptosis, a cell death process characterized by increased lipid peroxidation, plays an important role in AD-related toxicities. CMS121 is a small molecule developed against these aspects of neurodegeneration. Here we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 76 publications
(111 reference statements)
2
86
0
1
Order By: Relevance
“…Ates et al [ 171 ] showed in an animal model that inhibition of fatty acid synthase (FASN) by CMS121 decreased lipid peroxidation. CMS121 treatment reduced the levels of 15LOX2 in the hippocampus compared to those of untreated WT mice.…”
Section: Ferroptosis In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Ates et al [ 171 ] showed in an animal model that inhibition of fatty acid synthase (FASN) by CMS121 decreased lipid peroxidation. CMS121 treatment reduced the levels of 15LOX2 in the hippocampus compared to those of untreated WT mice.…”
Section: Ferroptosis In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Sphk2, another neuronal sphingosine kinase, also have been reported to protect against hippocampal volume loss and demyelination in male J20 mice ( Lei et al, 2019 ). Additionally, a fatty acid synthase inhibitor, CMS121, protects against ferroptosis-induced lipid peroxidation and alleviates cognitive impairment in APP/PS1-transgenic mice ( Ates et al, 2020 ). Taken together, these findings demonstrated that restoration of lipid peroxidation effectively rescued the AD-like symptoms and lipid metabolism pathway will be a potential therapeutic target for the prevention of this disease in the future.…”
Section: Ferroptosis-related Signaling Pathways In Admentioning
confidence: 99%
“…In a very recent paper by Ates et al [ 82 ], promising results were obtained using a fisetin derivative. The substance, CMS121, is a small molecule derived from fisetin, which is developed by a drug discovery paradigm based on phenotypic screening assays.…”
Section: Fisetinmentioning
confidence: 99%